Pathogenesis and Function of Interleukin-35 in Rheumatoid Arthritis - Xin, Pan Lin; Jie, Li Fan; Cheng, Qian; Bin, Du Yi; Dan, Cheng Wen (Frontiers in Pharmacology, 2021)
It is well known that RA (Rheumatoid arthritis) is an autoimmune disease characterized by multiple and symmetric arthropathy. The main pathological features of RA are synovial hyperplasia, angiogenesis, pannus formation, inflammatory cell infiltration, articular cartilage, bone destruction, and ultimately joint dysfunction, even deformity. IL-35 (Interleukin-35) is a new member of the IL-12 (Interleukin-12) family, which is an immunosuppressive and anti-inflammatory cytokine secreted mainly by Treg (T regulatory cells). There was evidence suggested that IL-35 could attenuate the development and progression of inflammation in RA through influencing the immune and pathological process of RA. It suggested that IL-35 played an important role in the pathogenesis of RA, and could be used as a potential target for the future treatment of RA. This review summarized the recent advances in the pathological roles and potential of IL-35 in the treatment of RA.